Η επίδραση της επεξεργασίας με υψηλή πίεση, στη μικροβιολογική ποιότητα των αλλαντιδίων Φρανκφουρτης, σε διαφορετικούς χρόνους εφαρμογής - Παρασκευά, Μαρία (Department of Agricultural Sciences, Biotechnology and Food Sciences, Cyprus University of Technology, 2013)
The terms fresh, healthy and natural are becoming more popular now than ever in food preservation technology. For this reason, mild preservation techniques that ensure minimum quality loss without compromising food safety are in the spotlight. Heat treatments combined with long processing times and addition of preservatives are giving way into new methods with High Pressure Processing (HPP) being one of the most effective. The purpose of this study was to assess the effectiveness of HPP at different times of application, on the quality of frankfurters. A total of ten samples were taken from the production process and were tested for the following microbiological parameters: (i) Total Viable Count (TVC), (ii) coliforms, (iii) E. coli and (iv) Bacillus cereus. All samples were stored at 4 οC until they were analysed. The results revealed no presence of Bacillus cereus in any of the samples tested. In experiments carried out we observed the presence coliforms and E.coli (numbers ranging from 2.52-5.54 log10cfu/g and 1.74-2.63 log10 cfu/g respectively), particularly in the initial samples prior to any treatment. Following the application of HPP coliforms were destroyed and the TVC was scientifically decreased. No significant differences were observed between HPP processed samples at different times. These results show that HPP can effective destroy coliforms and significantly reduce the TVC thus ensuring better microbiological quality products with a higher shelf-life.
Keywords: Food preservation; Material quality; Microbial